TEACHER TALK IN A BRITISH SITCOM: INSIGHTS FROM EMBODIED ACTIONS TO CLASSROOM INTERACTION COMPETENCE - Sugianto, Ahmad; Yusuf, Fazri Nur (LLT Journal: A Journal on Language and Language Teaching, 2023)
Teacher talk is one of the essential elements through which learning opportunities for pupils are facilitated. Nevertheless, to the best of the researchers’ knowledge, investigations regarding the ways a native teacher illustrated in a British Sitcom utilizes embodied actions that influence opportunities for learning characterized as classroom interaction competence are found to be limited. Thus, the present study aimed at unfolding the native teacher talk concerning the ways the teacher uses embodied actions along with verbal language to provide learning opportunities illustrated in a British Sitcom. By utilizing a conversation analysis approach, the artifact, namely a British Sitcom entitled Mind Your Language, was scrutinized. The findings revealed several embodied actions involving gesture, facial expression, and gaze accompanying the teacher's talk significantly facilitate and mediate the students’ learning.  Also, the skills and systems constitute the most frequently occurring mode whereas the least frequently occurring mode was the classroom context mode. Lastly, the study arrived at conclusions that the use of embodied actions is necessarily required for its significant functions and use for teacher talk that lead to classroom interaction competence.